284 Obesity and type I endometrial carcinoma: an overly simplified model?. (13th November 2020) - Liao, C; Richardson, M; Tran, K; Chan, C; Mann, AK; Maxwell, GL; Hamilton, CA; Tian, C; Darcy, K; Kapp, DS; Chan, JK
Abstract : Objective: To evaluate the relationship between obesity and incidence of type I endometrial cancer in two large population cohorts. Methods: From 2001 to 2016, incidence rates were estimated from United States Cancer Statistics data. Hysterectomy, pregnancy, and obesity rates were derived from the Behavioral Risk Factor Surveillance System (BRFSS). SEER*Stat and Joinpoint regression were used to calculate the incidence rate (per 100, 000). Results: A total of 531, 481 patients were diagnosed with endometrial cancer, and 385, 821 were diagnosed with grade 1 or 2 endometrioid histology (82% White, 6% Black, 8% Hispanic, 3% Asian). Women aged 65–69 had the highest incidence (80.31). Incidence was highest in White women (20.0), followed by Hispanics (15.1), Blacks (12.8), and Asians (9.9). The overall incidence of grade 1 and 2 endometrioid carcinoma decreased by 2% per year from 24.4 to 18.5 between 2001 and 2016 (p<0.001). Using survey data from BRFSS, from 2001 to 2016, the proportion of women with obesity increased from 21.1% to 30.2% (average annual increase of 2.3%, p<0.001). Black women had the highest proportion of obesity (47.5%), followed by Hispanics (33.7%), Whites (28.1%), and Asians (12.8%). However, there was no increase in either grade 1 or 2 endometrioid carcinoma incidence over the study period, and no association with the increase in obesity rate. Conclusion: Older and White women are at higher risk of grade 1 or 2 endometrial cancer. Our combined analyses suggest that the decreasing incidence of type I endometrial cancer is not correlated with the rise in obesity.